MALPRAKTIK DOKTER DALAM PERSPEKTIF UNDANG-UNDANG PRAKTIK KEDOKTERAN DAN HUKUM PERDATA - Adiartha, Aviyado Surya; Suryono, Arief (Jurnal Privat Law, 2023)
This article aims to determine the legal consequences of medical malpractice by doctors against patients in the perspective of Law Number 29 of 2004 concerning Medical Practice and civil law. The research method used is a prescriptive normative legal research method. The legal approach used is the statutory approach. Sources of legal materials used include primary and secondary legal materials with legal material collection techniques using literature study or document study. The results of this study indicate that the Medical Practice Law only regulates disciplinary sanctions for doctors on the decision of the Indonesian Medical Discipline Honorary Council (MKDKI) as a follow-up if there is a complaint from a patient against a doctor's actions that are considered detrimental, while the legal consequences must be borne by the doctor if proven to have committed medical malpractice it is not directly regulated by this law but is regulated by the Civil Code. The legal consequences of this medical malpractice cause the doctor's responsibility to the patient. This responsibility is in the form of liability for losses due to default or liability for losses due to illegal acts.